Mengembangkan kecerdasan berpikir, berbahasa, dan berolahraga melalui permainan tradisional - Bachtiar, Yudi; Sidiq, Burhan; Rizali, Ihsan (IKIP SILIWANGI, 2025)
This Community Service (PKM) activity aims to increase awareness of the people of Karangsinom Village, Karawang, about the urgency and benefits of preserving traditional games rooted in local culture. The activity was carried out in February 2025 involving 30 participants consisting of PKK mothers, elementary school teachers, and students. The implementation method includes workshops and traditional game practices. The Beam and Dagongan Races are the media for practice to integrate the three intelligences through traditional game sports. The evaluation results showed an increase in participants' understanding of the educational value of traditional games, as well as enthusiasm in implementing them in social and school environments. This activity proves that traditional games not only preserve culture, but are also effective as a holistic solution for developing thinking, language, and sports intelligence. Follow-up recommendations include ongoing training and integration of traditional games in the national curriculum. Keywords: Multiple intelligence, Traditional Games, Local Wisdom.